Strategi Pengembangan Usaha Jahit di Gampong Meutia Kota Langsa Ditinjau Menurut Ekonomi Islam - Fazilla, Fitri; Kamal, Safwan; Safarida, Nanda (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
This research was conducted with the aim of determining the strategy of sewing business development in Gampong Meutia Langsa City using qualitative methods. The research location in this study is on sewing entrepreneurs in Gampong Meutia, Langsa City. The subjects studied were 6 sewing entrepreneurs and village equipment in Gampong Meutia. Data collection techniques are carried out by observation, interviews and documentation. The technical data analysis used is descriptive analysis by going through the data collection stage through the data reduction stage, presenting data and drawing conclusions. The results of this study show that the sewing business in Gampong Meutia Langsa City is run by the business owner himself, where the business owner is fully responsible for management. The management of the sewing business in Gampong Meutia is quite good and the development of the sewing business in Gampong Meutia has developed quite well compared to neighboring villages, although there are still obstacles in several fields. The obstacles faced by sewing entrepreneurs in Gampong Meutia Langsa City are obstacles in capital, namely the difficulty of obtaining additional capital, obstacles in labor, namely the owner difficulty in obtaining labor, lack in the number of workers and lack of discipline of employees and obstacles in the use of machines. The business development strategy is to ask for additional capital and the government seeks this assistance and facilitates the community so that they succeed in getting the assistance through MSME assistance by making proposals, where the proposals are made as well and attractive as possible. And promote their efforts using social media. However, in terms of getting additional capital, these entrepreneurs still use conventional banks that apply credit interest rates. While the kerdit flower in Islam is included in riba which is prohibited by the Shari'a.